NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL KEKAL KARYA JALU KANCANA - Anggi Putri Pratiwi; Antonius Totok Priyadi; Agus Wartiningsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractA This research aims to improve the reader's understanding of the value of character education in the novel entitled Kekal by Jalu Kancana. It is a qualitative research with descriptive method qualitative with descriptive method. The data source of this research is the novel Kekal by Jalu Kancana, in the form of words quotations, phrases and sentences that lead to the object of analysis. The results indicated that the obtained data were amounted to 77 data. The obtained religious values were firm establishment, confidence, cooperation between religious leaders and beliefs, friendship, sincerity, loving the environment and protecting the small and sidelined. The obtained nationalism values were being competent and excellent, maintaining the environment, obeying the law, and being disciplined. The obtained self-reliance values were work ethic, tough and resilient, fighting power, creative, courage and being a learner throughout life. The obtained communal work values were respect, cooperation, inclusiveness, commitment to mutual decisions, consensus deliberation, favors, solidarity, empathy, non-violence, and volunteerism. The obtained integrity values were honesty, love for truth, loyalty, anti-corruption, responsibility, honesty, and respect for the dignity of individuals. The implementation plan of learning from the research result was combined with Indonesian language learning in grade of XII high school/level in curriculum 2013 with KD 3.9 analyzing novel texts both oral and written and KD 4.9 producing novel texts that were coherent in accordance with the characteristics of the text both spoken and written.Keywords: Character education, The Novel Kekal, Value